2016
DOI: 10.1136/heartjnl-2015-309067
|View full text |Cite
|
Sign up to set email alerts
|

Approach to residual pulmonary valve dysfunction in adults with repaired tetralogy of Fallot

Abstract: Residual right ventricular outflow tract and pulmonary valve disease is common in adults with repaired tetralogy of Fallot. Chronic severe pulmonary regurgitation as a result of surgical repair can lead to myriad complications including right ventricular dysfunction, decreased exercise tolerance, right heart failure and symptomatic arrhythmias. The aim of restoring pulmonary valve integrity is to preserve right ventricular size and function with the intent of mitigating the development of symptoms and poor lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 50 publications
0
20
0
6
Order By: Relevance
“…The pathophysiological changes underlying cardiac dysfunction in patients with Tetralogy of Fallot (TOF; pulmonary stenosis, overriding aorta, ventricular septal defect, right ventricular hypertrophy) have been the subject of ongoing investigation, as the optimal timing of follow‐up surgeries in these patients remains to be clearly defined . In particular, the timing and method for pulmonary valve replacement in patients with free pulmonary regurgitation (PR) after surgical repair using transannular patch remains controversial, as it requires a balance between maintaining right ventricular (RV) function and size on the one hand, and limiting the patient's exposure to multiple interventions throughout lifetime on the other …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiological changes underlying cardiac dysfunction in patients with Tetralogy of Fallot (TOF; pulmonary stenosis, overriding aorta, ventricular septal defect, right ventricular hypertrophy) have been the subject of ongoing investigation, as the optimal timing of follow‐up surgeries in these patients remains to be clearly defined . In particular, the timing and method for pulmonary valve replacement in patients with free pulmonary regurgitation (PR) after surgical repair using transannular patch remains controversial, as it requires a balance between maintaining right ventricular (RV) function and size on the one hand, and limiting the patient's exposure to multiple interventions throughout lifetime on the other …”
mentioning
confidence: 99%
“…11 In particular, the timing and method for pulmonary valve replacement in patients with free pulmonary regurgitation (PR) after surgical repair using transannular patch remains controversial, as it requires a balance between maintaining right ventricular (RV) function and size on the one hand, and limiting the patient's exposure to multiple interventions throughout lifetime on the other. 11,12 The development of tools to further characterize cardiac function with the aim to aid in the clinical management of TOF patients with PR is therefore of importance and has been explored in several studies. For example, investigators observed reduced right ventricular AVP movement in patients with PR following corrective surgery for TOF.…”
mentioning
confidence: 99%
“…При наличии выраженной гипоплазии кольца клапана легочной артерии требуется выполнение массивной инфундибулэктомии и трансаннулярной пластики, которая приводит к развитию выраженной легочной регургитации [15]. Последняя ведет к хронической объемной перегрузке правого желудочка, приводящей к прогрессирующей ди-латации и дисфункции правого желудочка [6,7,15,16]. Со временем у пациентов снижается толерантность к физической нагрузке, развиваются предсердные и желудочковые аритмии, а также появляется высокий риск внезапной сердечной смерти в течение 3-4 десятков жизни [17].…”
Section: дисфункция клапана легочной артерииunclassified
“…В случае коррекции тетрады Фалло с аномалиями коронарных артерий, ветви которых пересекают выходной отдел правого желудочка, единственной доступной опцией является имплантация кондуита. С течением времени происходит деформация и стеноз кондуита, который вследствие перегрузки давлением приводит к концентрической гипертрофии правого желудочка, повышению диастолического давления в его полости и повышению давления в правом предсердии [7]. Перегрузка давлением и гипертрофия правого желудочка -это факторы риска неблагоприятного исхода, включая устойчивую желудочковую тахикардию и случаи внезапной сердечной смерти в отдаленном периоде после радикальной коррекции тетрады Фалло [18].…”
Section: дисфункция клапана легочной артерииunclassified
See 1 more Smart Citation